Soluble CD163 is a biomarker for accelerated atherosclerosis in systemic lupus erythematosus patients at apparent low risk for cardiovascular disease. (2nd January 2020) - David, C; Divard, G; Abbas, R; Escoubet, B; Chezel, J; Chauveheid, MP; Rouzaud, D; Boutten, A; Papo, T; Dehoux, M; Sacre, K
Abstract : Objective : This study aimed to determine whether sCD163, a soluble macrophage marker up-regulated in numerous inflammatory disorders, is predictive of accelerated atherosclerosis associated with systemic lupus erythematosus (SLE). Methods : Carotid ultrasound was prospectively performed, at baseline and during follow-up, in 63 consecutive SLE patients asymptomatic for cardiovascular disease (CVD) and 18 volunteer health workers. Serum sCD163 level was determined at baseline using enzyme-linked immunosorbent assay. The primary outcome was the presence of a carotid plaque. Factors associated with carotid plaques were identified through multivariate analysis. Results : Despite a low risk for cardiovascular events according to Framingham score in both groups (2.1 ± 3.8% in SLE vs 2.1 ± 2.9% in controls; p = 0.416), ultrasound at baseline showed a carotid plaque in 23 SLE patients (36.5%) and two controls (11.1%) (p = 0.039). Multivariate analysis showed that SLE status increased the risk for carotid plaque by a factor of 9 (p = 0.017). In SLE patients, sCD163 level was high (483.7 ± 260.8 ng/mL vs 282.1 ± 97.5 ng/mL in controls; p < 0.001) and independently associated with carotid plaques, as assessed by stratification based on sCD163 quartile values (p = 0.009), receiver operating characteristics (p = 0.001), and multivariate analysis (p = 0.015). sCD163 at baseline was associated with the onset of carotid plaque during follow-up (3 ± 1.4 years) in SLE patients who had no carotid plaque at the first evaluation (p = 0.041). Conclusion : sCD163 is associated with progressing carotid plaque in SLE and may be a useful biomarker for accelerated atherosclerosis in SLE patients at apparent low risk for CVD.